The Influence of Human–Elephant Conflict on Electric Fence Management and Perception Among Different Rural Communities in Laikipia County, Kenya. Issue 4 (3rd July 2016) - Van Eden, Marcia; Ellis, Edward; Bruyere, Brett L.
ABSTRACT: Electrified fences are commonly used in Kenya to prevent human–elephant conflict. This research addressed the social perceptions of electrified wildlife fences by assessing community-level individual views of the fences and the willingness of community members' involvement in fence management. In Laikipia County, Kenya, a population sample of people in two communities living near an electrified fencing and experiencing different levels of human–elephant conflict (i.e., crop raids) were surveyed about their perceptions of the fence and fence management. Respondents in communities with more frequent conflict were less favorable in their ratings about fence effectiveness and were more willing to pay for fence maintenance. In addition, a sample group of pastoralists indicated a positive attitude toward the fence, due to a perceived improvement in livestock safety from predators and theft. These benefits appeared to outweigh the difficulties the fence could impose on livestock management and cross country travel.